The Problem of Non-Communicable Disease Service Policy During Covid -19 in Indonesia and Malaysia - Budiarsih, Budiarsih; Mangesti, Yovita Arie; Chaidar, Muhammad; Che Ngah, Anisah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This research aims to highlight the problem of NCD during the Covid -19 pandemic. In both Indonesia and Malaysia, NCDs are the number one killer that has caused tremendous stress on the healthcare system. Policies that focused on Covid only at that time created new problems for NCD. Restrictions on coming to the hospital made NCD patients not helped or try to treat themselves, this certainly had a negative and positive impact on NCD patients during Covid 19 in Indonesia and Malaysia. The research method used in this study is a socio-legal approach by examining various primary and secondary sources in the form of comparative studies with sources of legislation, books, journals, and online sources as well as interviews conducted at random among NCD patients to measure their response during the pandemic. Covid -19. The findings show that policies and management in Indonesia and Malaysia for NCD patients during COVID -19 have a negative and positive impact. Learning from the pandemic, both countries need to make regulations or laws during a pandemic or epidemic emergency so that people are protected.